2019
DOI: 10.1186/s40068-019-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Land use/cover spatiotemporal dynamics, driving forces and implications at the Beshillo catchment of the Blue Nile Basin, North Eastern Highlands of Ethiopia

Abstract: Background: Land use/cover (LULC) change is a dynamic and complex process that can be caused by many interacting processes ranging from various natural factors to socioeconomic dynamics . It exerts a strong influence on the structure, functions and dynamics of most landscapes. Monitoring and mapping of LULC dynamics are crucial as changes observed reflect the status of the environment and provide input parameters for optimum natural resources management and utilization. The objective of this study was to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 75 publications
8
49
0
Order By: Relevance
“…A similar study conducted in the northwestern part of Finchaa catchment also revealed that agricultural lands were expanding at the expense of forest and grassland [40]. This finding was also consistent with other research reports elsewhere in Ethiopia [15,19,22,37,48].…”
Section: Land Use/land Cover Changessupporting
confidence: 90%
See 2 more Smart Citations
“…A similar study conducted in the northwestern part of Finchaa catchment also revealed that agricultural lands were expanding at the expense of forest and grassland [40]. This finding was also consistent with other research reports elsewhere in Ethiopia [15,19,22,37,48].…”
Section: Land Use/land Cover Changessupporting
confidence: 90%
“…Since the resolution of the historical maps for 1987 obtained from the Ethiopian Mapping Agency was poor, a high resolution of Google Earth was used to better identify the land-use classes. A similar approach was used by different studies where the historical maps were poor in Ethiopia [21,22,[40][41][42][43] and Italy [44].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The signi cant linkage observed between NDVI and LULC changes, was used to estimate the forage biomass production trends across the rangeland compared to each LULC type [43][44][45]. This implies that there is a direct correlation between rainfall, vegetation greening and biomass production in Teltele rangeland [31]. If the rainfall was high, the vegetation cover of rangeland would be better as compared to the period when the rainfall was low or drought and from this, it can be understood that the greenery was also highly related with the losses of vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 90s, ecosystem services have become a central issue for researchers and decision-makers, especially after the Millennium Ecosystem Assessment report [10] addressed the gap between natural protection and human welfare [11]. Although consequences of LU/LC changes have been studied at a global level, these studies have not captured critical LULC changes occurring at the basin scale [12,13] including Wami River Basin.…”
Section: Introductionmentioning
confidence: 99%